Comparison of intrinsic brain activity in individuals with low/moderate myopia versus high myopia revealed by the amplitude of low-frequency fluctuations. (April 2020) - Cheng, Yi; Huang, Xin; Hu, Yu-Xiang; Huang, Mu-Hua; Yang, Bo; Zhou, Fu-Qing; Wu, Xiao-Rong
Background: Previous neuroimaging studies demonstrated that individuals with high myopia are associated with abnormalities in anatomy of the brain. Purpose: The purpose of this study was to explore alterations in the intrinsic brain activity by studying the amplitude of low-frequency fluctuations. Material and Methods: A total of 64 myopia individuals (41 with high myopia with a refractive error <–600 diopter [D], 23 with low/moderate myopia with a refractive error between –100 and –600 D, and similarly 59 healthy controls with emmetropia closely matched for age) were recruited. The amplitude of low-frequency fluctuations method was conducted to investigate the difference of intrinsic brain activity across three groups. Results: Compared with the healthy controls, individuals with low/moderate myopia showed significantly decreased amplitude of low-frequency fluctuation values in the bilateral rectal gyrus, right cerebellum anterior lobe/calcarine, and bilateral thalamus and showed significantly increased amplitude of low-frequency fluctuation values in left white matter (optic radiation), right prefrontal cortex, and left primary motor cortex (M1)/primary somatosensory cortex (S1). In addition, individuals with high myopia showed significantly decreased amplitude of low-frequency fluctuation values in the right cerebellum anterior lobe/calcarine/bilateral parahippocampal gyrus, bilateral posterior cingulate cortex, and bilateral middle cingulate cortex and significantly increased amplitude of low-frequency fluctuation values in left white matter (optic radiation), bilateral frontal parietal cortex, and left M1/S1. Moreover, we found that the amplitude of low-frequency fluctuation values of the different brain areas was closely related to the clinical features in the high myopia group. Conclusion: Our results demonstrated that individuals with low/moderate myopia and high myopia had abnormal intrinsic brain activities in various brain regions related to the limbic system, default mode network, and thalamo-occipital pathway.